Estudio exploratorio de validación del cuestionario “conductas observables en niñas y niños escolares con manifestaciones de inatención, hiperactividad/impulsividad” - Monge Rodríguez, Melania; Parrales Rodríguez, Sonia (Universidad de Costa Rica, 2017)
The school population with manifestations of inattention and hyperactivity / impulsivity often exhibit weak executive cognitive processes, which are often associated to the functionality of the individual, cognitive as well as emotional and behavioral. The "Questionnaire of Observable Behaviors of School Children with Inattention, Hyperactivity and Impulsivity" (CONMIHI) is an instrument that has been created with the objective of facilitating elementary school teachers, identify behavioral indicators that correlate to five executive cognitive processes such as self-regulation, inhibition, working memory, focused control, and volition; which are associated with students’ academic performance as well as efficiency on daily activities. For this, a quantitative type of research with a descriptive approach, type of survey, aimed at Costa Rican primary school teachers; was carried out. The sample type was non-probabilistic and 158 teachers from 15 schools located in eight counties of Costa Rica participated. The main objective was to carry out a validation exploratory study of the CONMIHI questionnaire. The temporary results show favorable scores: Cronbach's alpha was 0.943; the factor analysis showed that 16 factors accounted for 72% of the cumulative variance. On the other hand, the reproduced communities indicated that 68 of the 72 items of the questionnaire managed to replicate 60% of the initial variability. With these scores, it is recommended to repeat the study with a more representative sample, so that it´s usage can be generalized and the students will be able to receive the correspondence teaching approach.